UPAYA PEREDAMAN LAJU PENINGKATAN SUHU UDARA PERKOTAAN MELALUI OPTIMASI PENGHIJAUAN - Sangkertadi & Renny (EKOTON, 2013)
Urban activities are not controlled is one element of the causes of global warming, which affects the increase in air and water temperature in the city and surrounding areas. Increasing the total area of pavement materials and the use of metal or other materials that are reflective of solar radiation on the building envelope, is a consequence of consumption of construction technology recently. It was precisely to encourage the acceleration of the Urban Heat Island phenomenon. In addition, transport activities, industry and households in the city also produces various types of waste gases causing the greenhouse effect. The use of vegetation elements are inexpensive components that can inhibit the rate of increase in temperature in urban areas. Determination of the number of green basic coefficient (KDH), a minimum percentage of Forest City and Green Open Space (RTH), a strategic reason to face the effects of global warming, especially for the tropics and humid. This paper specifically raised the role of urban greening to fortify the system of sustainable development in the face of global warming.